Heavy Reliance on the Indirect Financing as Sources of Funds for Business Firms in Japan: As a Comparison for Indonesian Financial Crisis - Yulius Yulius (Bina Nusantara University, 2001)
The purpose of this article is to study the implication of financial liberalization to the heavy reliance of firms to the indirect finance in Japanese experience. In order to analyze the goal of this article, we start to examine the causes of the main bank system in Japan before and the pre-war period. Then, this article discusses the impacts of financial liberalization to the to the heavy reliance on the indirect-financing for business firms in the light with Japan’s financial market, particularly the main bank system. Finally, this article also discusses the implication of loose relationship of big firms and major banks (main bank system) to the recent financial condition in starting from the early of 1990s until now. This article discovered that financial liberalization, which started at the latter half of 1970s, has shaken the foundation of the main bank system. The major firms started to less dependent on the major banks and they issued the securities in domestic and international market. As a consequence, the SMBS still depend on the banks as their source of indirect financing. However, the competitiveness in the SMBS market turned to erode the bank profits that induced them to enter the risk activities, such as real estate. In addition, the bubble burst economy also triggered the boom in real estate. Naturally, as a nature of risk asset, loan to the real estate became the potential of bad loans that also was exacerbated the bubble burst in economy. Then, the financial crisis has revealed in 1990s.